Uma casa numa aldeia transmontana: Adaptar a arquitetura vernacular ao modo de projetar contemporâneo - Pedro Miguel Veigas Santos (2019)
This dissertation portrays the process that accompanied a rehabilitation project for housing in Vale de Couço, in the municipality of Mirandela, Bragança district. In the course of the work, a narration of the author's encounter with the various particularities determined by the client and the place, which characterize the space, is formed, in order to meet the fundamental issues connected to the act of dwelling and its relationship with the surrounding space. Starting from a generalized exposition, which then appropriates a more particular case study, the essential elements of a discourse that aims to inform about the project is developed. Assuming, in a final phase, the form of a project in a real context, the proposal presented for the transformation of this place portrays the synthesis between the premises associated with the client and the place, the personal convictions about the exercise of architectural design and the inherent limits to reality.